Integrating environmental, social and governance factors into the private equity investment : Evidence from Finnish private equity industry - Andreeva, Daria (My University, 2023)
Private equity (PE) companies increasingly recognise the importance of environmental, social, and governance (ESG) factors in their investment activities and strategies. This trend is driven by the urgent need for sustainable development and the growing consensus on the significance of addressing global problems. As companies acknowledge the need to tackle global challenges, ESG has become a critical consideration in their long-term objectives. Consequently, private equity companies are shifting towards responsible investing, which has led to changes in how they evaluate potential target companies. The integration of ESG factors has been identified as a potentially valuable practice for enhancing a company's long-term performance, risk management, cost savings, reputation, and stakeholder relations. Despite the well-known benefits, the challenges and risks associated with ESG integration are simultaneously hindering the development of sustainable practices. One of the underlying challenges is conducting a reliable analysis of a target company during the due diligence process. Another challenge of integrating ESG factors into private equity investments has been the need for standardisation of ESG reporting terms, making it difficult for investors to compare the sustainability of different target companies. One notable development in this area is the Sustainable Finance Disclosure Regulation introduced by the European Union in 2021, which has had a significant impact on private equity companies' and target firms' data disclosure obligations. This study investigates the integration of ESG factors into investment activities in the Finnish private equity industry. This study addresses both the drivers and the challenges of ESG integration to provide a more comprehensive overview of private equity companies' motives for integrating ESG factors into their investment strategies. The theoretical framework is built around three theories – stakeholder theory, shareholder theory, and principal-agent theory – which provide a comprehensive layout for examining the ESG integration in Finnish private equity companies. The theoretical section of this study also provides an overview of the three most common investment strategies: negative screening, impact investing, and thematic investing. The study maps different tools and strategies and compares existing theories with practice. This study is conducted using a qualitative research approach. The empirical data for this study was collected through semi-structured interviews with four Finnish private equity companies. The interview questions are divided into four sets according to their topic and themes. With the help of the qualitative coding method, this study analyses the empirical data and answer three sub-questions of this study, comprehending the typical investment process of private equity companies, understanding what kind of activities private equity companies engage in to promote ESG factors and identify the key challenges and risk mitigating tools of private equity companies.

Pääomasijoitusyritykset tunnistavat yhä enemmän ympäristöön, yhteiskuntavastuuseen ja hallintotapaan (ESG) liittyvien tekijöiden tärkeyden sijoitustoiminnassaan ja -strategioissaan. Tämä trendi syntyy kestävän kehityksen kasvavasta tarpeesta ja yhteisymmärryksestä globaalien ongelmien ratkaisemisesta. Samalla kun yritykset tunnistavat tarpeen käsitellä globaaleja haasteita, ESG-tekijät ovat vakiintuneet heidän pitkän aikavälin tavoitteissaan. Tämän seurauksena pääomasijoitusyhtiöt ovat ottaneet askeleen kohti vastuullisempaa sijoittamista, mikä on muovannut tapaa arvioida potentiaalisia sijoituskohteita. ESG-tekijöiden integrointi on tunnistettu tuovan potentiaalia yrityksen pitkäaikaisen suorituskyvyn, riskienhallinnan, kustannussäästöjen, maineen ja sidosryhmien välisten suhteiden parantamisen kannalta. Vaikka useat hyödyt ovat tunnettuja, ESG-integraatioon liittyvät haasteet ja riskit hidastavat kestävien hankkeiden kehitystä. Yksi perimmäisistä ESG-integroinnin haasteista liittyy luotettavan analyysin tekemiseen kohdeyrityksen due diligence -prosessin aikana. Toisena haasteena ESG-tekijöiden integroinnissa pääomasijoituksiin on ollut ESG-raportoinnin standardoinnin puute, mikä vaikeuttaa sijoittajien eri kohdeyritysten vastuullisuuden vertailua. Yksi merkittävä kehitys finanssialalla on Euroopan unionin vuonna 2021 esittelemä SFDR asetus, jolla on merkittävä vaikutus pääomasijoitusyritysten ja kohdeyritysten tiedonantovelvollisuuteen liittyen. Tämä tutkimus tutkii ESG-tekijöiden integrointia suomalaisessa pääomasijoitusyritysten toiminnassa. Tämä tutkimus käsittelee ESG-tekijöiden integroinnin ajureita ja haasteita sekä tarjoaa kattavan kuvan pääomasijoitusyhtiöiden motiiveista integroida ESG-tekijöitä sijoitusstrategioihinsa. Tutkimuksen teoreettinen viitekehys perustuu kolmeen teoriaan - sidosryhmäteoriaan, osakkeenomistajateoriaan ja päämies-agentti-teoriaan – jotka yhdessä tarjoavat kattavan perustan ESG-tekijöiden integroinnin tutkimiseen suomalaisissa pääomasijoitusyhtiöissä. Tutkimuksen teoreettinen osio tarjoaa myös yleiskatsauksen kolmesta yleisimmästä sijoitusstrategiasta: negatiivisesta seulonnasta, vaikuttavuussijoittamisesta ja temaattisesta sijoittamisesta. Tämä tutkimus toteutettiin käyttämällä laadullista tutkimusmenetelmää. Empiirinen aineisto kerättiin puolistrukturoiduilla haastatteluilla neljän suomalaisen pääomasijoitusyrityksen kanssa. Haastattelukysymykset on jaettu neljään osaan aiheiden ja teemojen mukaan. Laadullisen koodausmenetelmän avulla tutkimus analysoi empiiristä aineistoa ja vastaa kolmeen alakysymykseen, joiden avulla tämä tutkimus tutkii pääomasijoitusyritysten tyypillistä sijoitusprosessia, tunnistaa millaisia toimintoja yritykset integroivat edistääkseen ESG-tekijöitä ja havainnoimaa merkittävimmät haasteet ja riskien hallinnointiin liittyvät työkalut, joita pääomasijoitusyritykset hyödyntävät.
Keywords: private equity, ESG factors, private investments, sustainability, due diligence